Determinant of unmet need for family planning among adolescent and young women in Kenya: multilevel analysis using recent Kenyan demographic health survey - Beyene Sisay Damtew; Hinsermu Bayu Abdi; Beker Ahemed Hussien; Getahun Tiruye; Nafyad Tolossa Urgie; Beniam worku Yigezu; Sifan Ahmed Mohammed; Bezawit Melak Fente (Frontiers in Reproductive Health, 2025)
BackgroundUnmet need for family planning (FP) refers to the proportion of women who are fecund, sexually active, and wish to delay or limit childbearing but are not using any effective contraceptive method. Unmet need for FP remains a significant public health concern, particularly among young women aged 15–24 years. This study explores the determinants of unmet need for FP among young women.Method and materialThis study used data from the 2022 Kenyan Demography and Health Survey to investigate the relationship between various factors and a binary outcome variable of unmet need for family planning among adolescent young age group. A multilevel binary logistic regression model was used to analyze the data, accounting for the clustering effects of the survey data. The statistical significance of the relationships was assessed using adjusted odds ratios with 95% confidence intervals. The model with the lowest deviance was considered the best fit for the data.ResultMagnitude of unmet need family planning among adolescent young age in Kenya is 25% (95% CI: 24.5%–26%). Determinants of Unmet need for family planning are age 15–19 (AOR: 3.4, 95%CI (1.3–11), undecided desire number of children (AOR: 2.3, 95%CI: 1.4–2.1), age at first sex 15–29 (AOR: 2.7, 95%CI: 1.2–6.2), rural residency (AOR: 3.9, 95%CI: 1.1–14), high community level poverty (AOR: 2.1, 95%CI: 1.1–4.5).ConclusionThe study finds that 25% of young women in Kenya lack access to family planning. Factors like age, desired family size, early sex, rural life, and poverty contribute to this. These factors create barriers that hinder women's ability to plan their pregnancies and access necessary resources. Younger women, those in rural areas, and those living in poverty are particularly affected. Addressing this issue requires a comprehensive approach that considers the specific circumstances of these vulnerable populations.